Antara Mitos dan Kesehatan: Praktik Pijat Bayi Tradisional Pada Ibu dengan Bayi Usia 0–12 Bulan - Aim Nadhiroh; Firdausi Nuzula; Nur Hidayatul Ainiyah; Syuhrotut Taufiqoh (Journal Center of Research Publication in Midwifery and Nursing, 2026)
Background: Infant massage is a complementary therapy that supports infant comfort and development. However, infant massage practices in the community are still predominantly performed by traditional practitioners and influenced by sociocultural factors, family experiences, and myth-based beliefs. Studies integrating traditional infant massage practices, information sources, and myth beliefs within community midwifery services remain limited. Methodology: This quantitative descriptive study with a cross-sectional approach was conducted at TPMB Farida Hajri Surabaya in December 2025. The study involved 19 mothers with infants aged 0–12 months selected using total sampling. Data were collected through a structured questionnaire covering respondent characteristics, infant massage information sources, massage practices, and myth beliefs. Data were analyzed descriptively using frequency and percentage distributions. Results: Most mothers were aged 20–35 years (84%). A total of 74% had received information about infant massage, mainly from family members or close relatives (57%). Most mothers had practiced infant massage (63%), and all practices were performed by traditional practitioners. Myth beliefs identified included infant fussiness due to sawanen (67%), fatigue (25%), and sprain (8%). Conclusion: Infant massage practices remain influenced by cultural factors and family-based information. Midwives should develop safe infant massage education using family-centered and culturally sensitive approaches to improve acceptance of evidence-based midwifery practices